The Impact of Disruptions in Food and Energy Supply Chains during International Armed Conflicts and the Means of Public International Law to Maintain Their Stability - Munsoor, Almoatuz Ahmed (Journal of Ecohumanism, 2025)
The research discussed the effects of disruptions in food and energy supply chains during international armed conflicts, their relevance to the concept of international peace and security, and the impact of these disruptions on the international economy and trade, as well as on relations between states, and on social peace and security. The research also examined the means of Public International Law to maintain the stability of these supply chains to prevent or mitigate these effects. The research adopted descriptive and inductive approaches to understand the link between supply chains and international peace and security, and to demonstrate their impact on the various axes discussed in the first chapter of the research. The descriptive and analytical approaches are used in the second chapter to describe the means of public international law and assess their effectiveness. The research concludes that there are effects on the international economy and trade, such as scarcity, lack of access, and unavailability. It also concluded that these disruptions negatively affect international relations through using food and energy sources as strategic weapons and negatively impact social peace and security by increasing crime rates, displacement, and illegal migration, among other effects. The research also concluded that there are relatively effective means of public international law to maintain the stability of these supply chains, with some playing a preventive role and others a remedial role.